Learning to Read Empirical Articles - Ammons, Samantha (TRAILS: Teaching Resources and Innovations Library for Sociology, 2013)
Through a series of low-stakes assignments, students are required to read, assess, and properly cite four peer-reviewed empirical research articles. The articles reflect the four core methodologies that we devote the most time to in class (surveys, fieldwork, secondary data, and content analysis). By reading and answering questions, student’s knowledge of research design & concepts specific to particular forms of methodology are reinforced, and students gain confidence reading full-length, scholarly, empirical research articles. They also learn to correctly construct a bibliographic reference using ASA formatting. Discussion of each article occurs we learn about each specific form of methodology in the course.